Cryopreserved Alginate-Encapsulated Islets Can Restore Euglycemia in a Diabetic Animal Model Better than Cryopreserved Non-encapsulated Islets. (12th September 2019) - Kojayan, Greg G; Flores, Antonio; Li, Shiri; Alexander, Michael; Lakey, Jonathan RT
Islet transplantation has been shown to restore normoglycemia clinically. One of the current limitations to the widespread clinical use of islet transplantation is culturing and preserving more than 1 million islet equivalents in preparation for transplant. One possible solution is to bank frozen islets and use them when needed. Although promising, the standard islet freezing protocol introduces stress and cell death, resulting in high variability of islet quality post thawing. This study aimed to develop an improved cryopreservation protocol using alginate-encapsulated islets to improve islet survival and function for future transplants. Our data showed that encapsulation improved islet survival and function after thawing the frozen islets. Frozen encapsulated islets have an islet yield recovery of 84% when compared to non-encapsulated islets at 72% after thawing. Post-thaw viability was 78% for non-encapsulated islets compared to 88% for encapsulated islets. The stimulation index values after a static glucose test following thawing were 1.9 ± 0.5, 2.9 ± 0.1, and 3.3 ± 0.3 for the non-encapsulated, 1.75% alginate, and 2.5% alginate groups, respectively. In a transplant study, the mice that received 1.75% alginate-encapsulated cryopreserved islets achieved normoglycemia on average 5 days after transplant. In comparison, control mice that received fresh islets took 4 days, while those receiving unencapsulated cryopreserved islets took 18 days. In conclusion, encapsulating islets in 1.75% alginate prior to freezing was shown to improve islet survival, function post thawing, and graft response significantly when compared to islets frozen without encapsulation.